G86(P) Paediatric advanced trauma skills (pats): a new advanced trauma course for multidisciplinary staff. (27th April 2015) - Anpananthar, A; Parikh, A; Masud, S; Edmonds, N; Makins, E
Abstract : Background: Major paediatric trauma is rare and therefore exposure to it is often sporadic and infrequent. Since the designation of major trauma centres (MTC), doctors in these centres are likely to see more paediatric trauma. Advances in paediatric trauma management and are not taught in the more traditional courses such as APLS, ATLS and ETC. This course has been designed for those with an interest in paediatric trauma based in either MTCs or major trauma units (MTU). There are no other similar courses at present in England. Method: We initially designed a 1-day high fidelity simulation course. Following 8 courses, it became clear there was a need to cover advanced trauma skills. PATS was subsequently developed as a 2-day course covering essential advanced skills. It is run with senior multidisciplinary faculty from emergency medicine, pre-hospital care, paediatric emergency medicine, surgeons, anaesthetists and paediatric intensive care. This high-fidelity simulation course incorporates technical and non-technical skills. The candidates completed anonymous pre- and post-questionnaires. Results: Of the 10 candidates who have attended the 2 courses, many had requested at the start of the course for more experience with complex trauma scenarios, procedures and leading the team. Despite 70% of the candidates having been involved in other trauma training courses and feeling confident in managing an injured child prior to this course, 90% found the course positively challenging and 100% reported that this course had met their expectations. All candidates had identified human factors as their main learning, in particular communication and team leadership. Other key themes identified were an increased confidence with specific procedures and management protocols. Practicing more procedures during scenarios was requested. Candidates had commented on the benefits of having a mixed seniority of the candidate group (senior trainees and consultants) and the faculty. Discussion: The feedback has been overwhelmingly positive. Evaluation demonstrated the importance of this course for multi-grade and multidisciplinary staff seeing paediatric trauma. Future courses will invite staff from all disciplines exposed to paediatric trauma and will address the request for more practical procedures.